Analisis Efektivitas Penggunaan Aplikasi Hospital Information System Atas Penerimaan Kas Pada Rumah Sakit Islam Ibnu Sina - Dinda Mustika Triwardani; R. Septian Armel (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
In the era of business digitization and globalization, the role of accounting information systems has become a key pillar in managing the financial operations of a company. One critical aspect that requires close monitoring is cash receipts, an essential element in measuring the financial health of an organization. The process of recording, managing, and reporting cash receipts through the accounting information system reflects the readiness level of a company in facing financial challenges. This research aims to assess the level of adoption and utilization of information technology at Ibnu Sina Islamic Hospital by using the Hospital Information System application for cash receipts as a key factor in enhancing its effectiveness. The study employs a qualitative descriptive approach to analyze the effectiveness of the Hospital Information System (HIS) application on cash receipts at Ibnu Sina Islamic Hospital in Pekanbaru. Primary data is obtained through in-depth interviews with the accounting staff at Ibnu Sina Islamic Hospital. The research findings indicate that the Hospital Information System application for cash receipts at Ibnu Sina Islamic Hospital plays a significant role in improving cash receipts. The strategies employed to overcome challenges reflect Ibnu Sina Islamic Hospital's commitment to providing more efficient healthcare services focused on patients. By involving all relevant parties, the hospital has successfully faced obstacles and laid a solid foundation for a more digital future in the healthcare industry.